Activity Management System (AMS) using Self-explanatory components / Nur Nabilah Husna Mohd Marzuki - Mohd Marzuki, Nur Nabilah Husna (2016)
The purpose of this project is to identify the current process and problems faced by ILD at UiTM Terengganu Kampus Dungun in providing information and generate reports of activities. Therefore, the solution to reduce the problems that had been identified was by developing Activity Management System (AMS). Nine Self-explanatory screen’ components were incorporated in system development. Among the elements were calendar form, use of icons and images, help screen and label of field. 3 phases were used in completing the project which were Analysis, Development and Testing. Waterfall model was used in developing the system. Users and experts tested the usability and functionality of the system. The results from the user evaluation shows the highest mean of 3.83 (SD=0.65) on usefulness, 3.83 (SD=0.75) on ease of use, 3.73 (SD=0.64) on consistency, 3.77 (SD=0.68) on ease of learning, 3.90 (SD=0.71) on satisfaction and 4.00 (SD=0.64) on interface. Overall, users agreed and satisfied with the system. Recommendation also obtain from the evaluation to improve the system in the future so that the system can meet the whole requirement needed. Among the recommendation where there are clickable calendar and able to provide the public holiday.